PULMONARY CRYPTOCOCCOSIS IN AIDS PATIENTS: RADIOGRAPHIC APPEARANCES AND SOME CLINICAL ASPECTS - VEERAPAND, Praparnrat; SUPANNACHART, Ponglada; FUANGTONG, Pairote; TUNGSAKULVATTANA, Sutharat (The ASEAN Journal of Radiology, 2023)
PURPOSES: To study radiographic appearances and some clinical aspects of pulmo- nary cryptococcosis in AIDS patients. MATERIALS AND METHODS: Medical records and chest radiographs were retro- spectively reviewed during October 1990 to February 1996 RESULTS; Pulmonary cryptococcosis were diagnosed in 22 patients with AIDS (21 men, 1 woman; age range 22-64 years). Fever, cough, headache and dyspnea were the main presenting symptoms. The most common radiographic appearance was diffusely mixed interstitial infiltration, predominantly fine or intermediate pattern (12/22). Bilat- eral coarse interstitial infiltration were noted in 2 patients, localized infiltration in 6 patients, unilateral pleural effusion with questionable infiltration in 1 patient and me- diastinal adenopathy alone in 1 patient. Associated minimal pleural effusion and cavi- ties were found as associated lesions in 5 and 2 patients respectively. Seventeen patients had concurrent cryptococcal meningitis with or without cryptococcal infection of other organs and 2 patients had cryptococcemia. Four cases could be diagnosed as pulmonary cryptococcosis prior to cryptococcal meningitis. Of the 18 patients receiving antifungal drugs, 13 patients improved and 5 patients died. The remaining 4 patients who had no specific treatment were all dead. Pulmonary cryptococcosis should be the considered diagnosis more frequently in AIDS patients. In the presence of cryptococcal meningitis with abnormal chest radiograph, the earlier it was diagnosed, the better will be the treatment outcome. Cryptococcal neoformans infection at the present time has been an important problem accompanying world-wide spread of the HIV virus. It is the fourth most common sys- temic opportunistic infection in patients with AIDS in USA' whereas it is the second most common in Thailand following tuberculosis. The organisms usually infect meninges and brain but many other organs could also be involved particularly the lung.3 The preva- lence of pulmonary cryptococcosis is expected to increase. Hence the purposes of this study are to describe radiographic appearance of pulmonary cryptococcosis in compari- son with others and to describe some aspects of clinical manifestations.